A comparative study on the adoption of IR 4.0 technologies in Malaysian TVET institutions - Mafarja, Nofouz; Mohamad, Mimi Mohaffyza; Ibrahim, Badaruddin; Sern, Lai Chee; Kiong, Tee Tze (LPMPP Universitas Negeri Yogyakarta, 2026)
In Malaysia, Technical and Vocational Education and Training (TVET) institutions play a crucial role in preparing the future workforce to thrive in the era of Industrial Revolution 4.0 (IR 4.0). This study presents a comprehensive comparative analysis of the adoption and integration of IR 4.0 technologies in Malaysian TVET institutions. It employs a quantitative approach using descriptive statistics and multivariate analysis of variance (MANOVA). The survey was conducted among 59 participants from three TVET institutions in Malaysia to gather data on the types and extent of IR 4.0 technologies implemented. The results indicate that, on average, all institutions demonstrated an intermediate level of adoption. However, there were significant differences in infrastructure and connectivity among the three institutions, while no significant differences were found in terms of intelligence-related technologies. The findings of this comparative study offer valuable insights into the adoption of IR 4.0 technologies in Malaysian TVET institutions.